Agapornis sp. pet birds: Source of dissemination of azole-resistant yeasts - Reis, Eduardo J. C. [UNESP]; Buscariolo, Fabio; Siqueira, Joao P. Z.; Castilho, Elza M.; Almeida, Margarete T. G. (Oxford Univ Press, 2019)
The objectives of this study were to identify yeasts in 40 feces samples of Agapornis birds and determine their antifungal susceptibility profile by two methodologies. Results indicated 92.5% of positivity (46 isolates). Six genera were identified (14 species): Cryptococcus (39.13%), four species; Candida (36.96%), four species; Rhodotorula (13.05%), two species; Trichosporon (6.52%), two species; Kodamaea ohmeri (2.17%); and Sporobolomyces salmonicolor (2.17%). Regarding the susceptibility profiles, 41.3% of the isolates showed low sensibility to fluconazole and 47.8% to itraconazole. Thus, Agapornis sp. disseminate potentially pathogenic and resistant yeasts. Precautionary measures should be taken regarding breeding and keeping them as pets.
Keywords: Agapornis; yeasts; Cryptococcus; Candida; antifungal susceptibility testing